REVOLUSI DIGITAL: Meningkatkan Kompetensi Pendidik MAN 2 Langsa di Era Teknologi - Nisa, Khairun; Nasir, Mohd.; Yacoeb, Anwar (Islamijah: Journal of Islamic Social Sciences, 2025)
The development of the digital era has brought significant changes in various aspects of life, including the world of education. This research discusses the transformation of MAN 2 Langsa educators' competencies in facing the digital era, which is marked by technological advances and digitalisation of education. The purpose of this study is to describe changes in the roles, learning methods, and skills of educators in response to the demands of the times. A descriptive qualitative approach was used with data obtained through interviews, participatory observation, and documentation. The results showed that educators at MAN 2 Langsa have undergone significant transformation in three main aspects: (1) The role of educators, (2) Learning methods, and (3) Improvement of educators' skills. This study confirms that this transformation is not only an adaptation to technology, but also an effort to improve the quality of education through an approach that is more interactive and relevant to the needs of the times. The findings provide important insights for the development of educator training policies to effectively support digital transformation.Keywords: Digital Era, Educator Competency Transformation, MAN 2 Langsa, Learning Methods